Student-teachers’ ICT Skills and their Use during Placement Related to Pre-Service Teacher Education Program at Yarmouk University in Jordan - Jawarneh, Tariq; El-Hersh, Ayed (Jordan Journal of Educational Sciences, 2005)
Identifying Pre-service teachers’ Information and Communication Technology (ICT) skills and the degree to which they apply these skills in their teaching is a vital issue both to inform future planning and to implement new ICT in educational systems in Jordan and worldwide. This study investigates ICT skills of student-teachers at Yarmouk University in Jordan and their degree of ICT use in practice schools during the first semester of 2003/2004 academic year. Data were obtained via questionnaires with a random sample of the (90) student-teachers and interviews with a random sample of (40) student-teachers. In addition, interviews with all teacher trainers (22) at Yarmouk University were conducted to further triangulate findings from studentteachers’ questionnaires and interviews. Regarding ICT skills the results showed that student-teachers possessed low to moderate ICT skill levels. With regard to the degree of ICT use at practice schools, results from the questionnaires showed congruency between student-teachers’ ICT skills level and the degree to which they apply these skills. However, results from the interviews indicated lack of ICT skills used by student-teachers during their teaching practice. Lack of adequate training at the university, lack of access to ICT resources, teacher-trainers’ inability to model the use of ICT in their teaching and inability to incorporate ICT in teaching were among the factors that affected student-teachers’ ICT use at practice schools.